Doctor–couple communication during assisted reproductive technology visits. Issue 5 (2nd April 2018) - Leone, D; Borghi, L; Del Negro, S; Becattini, C; Chelo, E; Costa, M; De Lauretis, L; Ferraretti, A P; Giuffrida, G; Livi, C; Luehwink, A; Palermo, R; et al.
Abstract: STUDY QUESTION: What are the characteristics of doctor–couple communication content during actual ART visits? SUMMARY ANSWER: Physicians were mainly focused on providing biomedical information, while communication content from couples had a 2-fold focus on providing biomedical information and on positive talk. WHAT IS KNOWN ALREADY: Communication aspects in ART seem crucial for clinical decision-making, retention in care and critical conversations with couples due to low treatment success rates. However, no studies have been carried out on the actual interaction between the doctor and the couple in this context. STUDY DESIGN, SIZE, DURATION: This observational study involved 28 clinicians and 160 patients referred to eight Italian ART clinics during a one-year recruitment period. PARTICIPANTS/MATERIALS, SETTING, METHODS: ART visits at eight Italian clinics were videotaped. The visits were coded using the Roter Interaction Analysis System (RIAS), particularly focusing on RIAS composite categories, verbal dominance and patient-centeredness score. MAIN RESULTS AND THE ROLE OF CHANCE: A total of 85 visits were eligible for analysis (62% acceptance rate), involving 28 clinicians and 160 patients (including 75 couples). The average visit duration was 37 ± 17.7 min. The mean verbal dominance was 1.9 ± 0.86 (range: 0.72–5.74). Physicians mainly focused on providing biomedical information. Communication content from couples had a 2-fold focus on providing biomedical information and on positive talk. The mean of patient centeredness index (PCI) was 0.51 (SD = 0.28; range 0.08–1.77); visits in which the doctor was a woman or the treatment indication was for heterologous fertilization showed higher PCI scores. Overall, females accounted for 67% of all patient talk. Taking this imbalance into account as expected frequencies for each composite category, males reported significantly more utterances in almost all of the socioemotional categories. LIMITATIONS, REASONS FOR CAUTION: These results are preliminary and observational and only regard Italy. Communication during visits may have been biased since the professionals who agreed to participate showed an interest in communication issues. Another limitation is a possible Hawthorne effect due to the fact that participants were aware of being videotaped. WIDER IMPLICATIONS OF THE FINDINGS: Our study showed that ART physicians mainly adopted an informative model of communication and a more disease-oriented approach. Findings revealed the complexity of communication content during ART consultations, given its triadic characteristic in which the third party is also a patient; clinicians should be aware of this complex aspect and of the specific male and female perspectives to be taken into account. The results could be useful for training ART professionals. STUDY FUNDING/COMPETING INTEREST(S): This study was possible thanks to an unconditional grant from Ferring Spa to the Department of Health Sciences, University of Milan. There are no competing interests to declare. TRIAL REGISTRATION NUMBER: N/A.